2007
DOI: 10.1152/ajpgi.00299.2007
|View full text |Cite
|
Sign up to set email alerts
|

Development and Physiological Regulation of Intestinal Lipid Absorption. II. Dietary lipid absorption, complex lipid synthesis, and the intracellular packaging and secretion of chylomicrons

Abstract: Research in dietary fat absorption has developed urgency because of the widely recognized epidemic of obesity in the United States. Despite its clinical importance, many controversies exist over some of the basic aspects of this process from the mechanisms of fatty acid uptake to the control of triacylglycerol export in chylomicrons. Recent advances have included the identification of a number of fatty acid transporters, the discovery of families of acyl-CoA synthetase long chains and acyltransferases, a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
117
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 25 publications
0
117
0
10
Order By: Relevance
“…The first step in lipid absorption, the movement of monoacylglycerols and fatty acids across the apical membrane of enterocytes, is not well defined on a molecular level; it very likely involves different mechanisms. Several studies describe protein-dependent mechanisms, although others have reported protein-independent transport via diffusion through the apical membrane of the enterocytes (39,40) for which in particular bile salts appear to be necessary as they form micelles with the fatty acids and facilitate thereby their absorption (41). Lipids also might be taken up via endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in lipid absorption, the movement of monoacylglycerols and fatty acids across the apical membrane of enterocytes, is not well defined on a molecular level; it very likely involves different mechanisms. Several studies describe protein-dependent mechanisms, although others have reported protein-independent transport via diffusion through the apical membrane of the enterocytes (39,40) for which in particular bile salts appear to be necessary as they form micelles with the fatty acids and facilitate thereby their absorption (41). Lipids also might be taken up via endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…MTP is modulated by several factors and typically regulated at the transcriptional level [50,51]. The newly synthesized chylomicron particle consists of apoB48, apoAIV, cholesteryl ester, triacylglycerol and phospholipid [52]. Newly synthesized, correctly folded nascent lipoproteins are transported from the ER unidirectionally to the concentrations in the plasma in association with triglyceride rich lipoproteins and HDL.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%
“…The uptake of cholesterol and long-chain fatty acids across the BBM is mediated both by passive transport and by BBM transporters [20,21]. Once lipids are in the enterocytes, they may be metabolized or transported out of the cell.…”
Section: Introductionmentioning
confidence: 99%